The use of thermal hydrogen decrepitation to recycle Nd-Fe-B magnets from electronic waste - Piotrowicz, Andrzej; Pietrzyk, Stanisław; Noga, Piotr; Myćka, Łukasz (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Rare earth magnets based upon neodymium-iron-boron (NdFeB) are employed in many high tech applications, including hard disk drives (HDDs). The key elements in manufacturing NdFeB magnets are rare earth elements (REEs) such as neodymium. This element have been subject to significant supply shortfalls in the recent past. Recycling of NdFeB magnets contained within waste of electrical and electronic equipment (WEEE) could provide a secure and alternative supply of these materials. Various recycling approaches for the recovery of sintered NdFeB magnets have been widely explored. Hydrogen decrepitation (HD) can be used as an direct reuse approach and effective method of recycling process to turn solid sintered magnets into a demagnetised powder for further processing. In this work, sintered Nd-Fe-B magnets were processed without prior removal of the metallic protective layer using the thermal HD process as an alternative recycling method. The gas sorption analyzer have been used to determine the quantity of the hydrogen absorbed by a samples of magnets, under controlled pressure (1, 2, 3 and 4 bar) and temperature (room, 100, 300 and 400 0C) conditions, using Sieverts’ volumetric method. The composition and morphology of the starting and the extracted/disintegrated materials were examined by ICP, XRD and SEM-EDS analysis.